Efektivitas Asas Peradilan, Sederhana, Cepat dan Biaya Ringan dalam Perkara Eksekusi di Pengadilan Agama Banjarbaru - Ruhansyah Ruhansyah; Jalaluddin Jalaluddin; Amelia Rahmaniah (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The principle of a fast, simple, and low-cost judiciary constitutes a fundamental principle in the administration of judicial power, as stipulated in Article 2 paragraph (4) of Law Number 48 of 2009 on Judicial Power. This principle aims to ensure access to justice for justice seekers, including in the enforcement of court judgments through execution mechanisms. However, in practice, execution proceedings often encounter various obstacles that cause the process to be slow, complicated, and costly. This study aims to analyze the effectiveness of the implementation of the principle of a fast, simple, and low-cost judiciary in execution cases at the Banjarbaru Religious Court and to identify the factors influencing its implementation. The research method employed is empirical legal research using a sociological-juridical approach. The results of the study indicate that the implementation of the principle of a fast, simple, and low-cost judiciary in execution cases at the Banjarbaru Religious Court has not yet been fully effective. This is due to juridical factors, non-juridical factors, as well as the level of legal awareness of the parties involved. Therefore, improvements are necessary in terms of regulatory frameworks, judicial administration, and the enhancement of public legal awareness in order to achieve effective and equitable execution of court judgments.